Safety and efficacy of a feed additive consisting of disodium 5'‐inosinate (IMP) produced by Corynebacterium stationis KCCM 80235 for all animal species (CJ Europe GmbH) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Fašmon Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2022)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of disodium 5’‐inosinate (IMP) produced by fermentation using Corynebacterium stationis KCCM 80235 as a sensory additive (flavouring compound) in feed and water for drinking for all animal species. The production strain is genetically modified, and it is resistant to streptomycin. No viable cells were detected in the final product. However, uncertainties remained on the genetic basis of the streptomycin resistance and on the possible presence of recombinant DNA from the production strain in the final product. Therefore, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) could not conclude on the safety of the additive for the target species, consumers, users and the environment. Moreover, the FEEDAP Panel reiterated its previous concerns on the safety of the use of IMP in water for drinking due to hygienic reasons. The Panel concluded that the additive is efficacious to contribute to the flavour of feed and water for drinking.